1995
DOI: 10.1128/iai.63.9.3502-3506.1995
|View full text |Cite
|
Sign up to set email alerts
|

Entry and survival of Leishmania amazonensis amastigotes within phagolysosome-like vacuoles that shelter Coxiella burnetii in Chinese hamster ovary cells

Abstract: Coxiella burnetii, a rickettsia, and Leishmania amazonensis, a protozoan flagellate, lodge in their host cells within large phagolysosome-like vacuoles. In the present study, C. burnetii-infected Vero or CHO cells were superinfected with L. amazonensis amastigotes to determine if these parasites can home to and survive within heterologous vacuoles. Six hours after superinfection, Leishmania amastigotes were located almost exclusively within large Coxiella-containing vacuoles. Thereafter, the numbers of parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Coinfection studies also provide information regarding the nutritional character and toxicity of PVs. M. avium, L. amazonensis and T. cruzi efficiently replicate in the Coxiella PV (Veras et al, 1995;Gomes et al, 1999;Andreoli et al, 2006), while M. tuberculosis does not. Interestingly, type IV secretion-deficient Legionella dotA mutants traffic to the Coxiella PV where they survive but fail to replicate (Sauer et al, 2005).…”
Section: Insight From Coinfection Of Cultured Cells With Coxiella Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Coinfection studies also provide information regarding the nutritional character and toxicity of PVs. M. avium, L. amazonensis and T. cruzi efficiently replicate in the Coxiella PV (Veras et al, 1995;Gomes et al, 1999;Andreoli et al, 2006), while M. tuberculosis does not. Interestingly, type IV secretion-deficient Legionella dotA mutants traffic to the Coxiella PV where they survive but fail to replicate (Sauer et al, 2005).…”
Section: Insight From Coinfection Of Cultured Cells With Coxiella Andmentioning
confidence: 99%
“…A common theme of these three pathogens is that their respective nascent phagosomes disconnect from the endocytic cascade soon after infection (Heinzen et al, 1996;Sinai et al, 2000;Roy et al, 2006). In contrast, mature Coxiella PV readily fuse with parasite vacuoles that remain in the endocytic pathway, including those of Mycobacterium avium (de Chastellier et al, 1999;Gomes et al, 1999), Mycobacterium tuberculosis (Gomes et al, 1999), Salmonella enterica (Drecktrah et al, 2007), Leishmania amazonensis (Veras et al, 1995) and Trypanosoma cruzi Fig. 2.…”
Section: Insight From Coinfection Of Cultured Cells With Coxiella Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusion between lysosomes and nascent phagosomes harbouring viable C. burnetii takes about 4 h, while fusion between lysosomes and phagosomes containing latex beads or inactivated C. burnetii occurs within 30 min (Howe and Mallavia, 2000). C. burnetii PV demonstrate promiscuous homotypic and heterotypic fusion with endolysosomal vacuoles, a process that presumably provides membrane for the expanding PV and nutrients for pathogen replication (Veras et al ., 1994;1995;Howe et al ., 2003). C. burnetii PV further deviate from typical endosomal maturation by interacting with the autophagy pathway to acquire some characteristics of autophagolysosomes (Beron et al ., 2002;Gutierrez et al ., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, coinfection studies have shown that PVs formed by L. amazonensis amastigotes can fuse with C. burnetii PVs but not with PVs containing L. major amastigotes, suggesting that the intracellular niches generated by Leishmania mexicana complex parasites and Coxiella may be compositionally rather similar(Real et al 2010;Beare et al 2011;Veras et al 1995;Rabinovitch and Veras 1996;Newton and Roy 2011).Both Coxiella and Leishmania actively participate in the creation of their respective PVsWaller and McConville 2002). To begin to understand how the two distantly related pathogens generate phenotypically similar PVs,…”
mentioning
confidence: 99%